Highly Efficient Microcell‐Mediated Transfer of HACs Containing a Genomic Region of Interest into Mammalian Cells. Issue 9 (7th September 2021) - Liskovykh, Mikhail; Larionov, Vladimir; Kouprina, Natalay
Abstract: Human artificial chromosomes (HACs) are considered promising tools for gene delivery, functional analyses, and gene therapy. HACs have the potential to overcome many of the problems caused by the use of viral‐based gene transfer systems, such as limited cloning capacity, lack of copy number control, and insertional mutagenesis during integration into host chromosomes. The recently developed alphoid tetO ‐HAC has an advantage over other HAC vectors because it can be easily eliminated from dividing cells by inactivation of its conditional kinetochore. This provides a unique control mechanism to study phenotypes induced by a gene or genes carried on the HAC. The alphoid tetO ‐HAC has a single gene acceptor loxP site that allows insertion of an individual gene of interest or a cluster of genes of up to several Mb in size in Chinese hamster ovary (CHO) hybrid cells. The HACs carrying chromosomal copies of genes can then be transferred from these donor CHO cells to different recipient cells of interest via microcell‐mediated chromosome transfer (MMCT). Here, we describe a detailed protocol for loading a gene of interest into the alphoid tetO ‐HAC vector and for the subsequent transfer of the HAC to recipient cells using an improved MMCT protocol. The original MMCT protocol includes treatment of donor cells with colcemid to induce micronucleation, wherein the HAC becomes surrounded with a nuclear membrane. That step is followed by disarrangement of the actin cytoskeleton using cytochalasin B to help induce microcell formation. The updated MMCT protocol, described here, features the replacement of colcemid and cytochalasin B with TN16 + griseofulvin and latrunculin B, respectively, and the use of collagen/laminin surface coating to promote attachment of metaphase cells to plates during micronuclei induction. These modifications increase the efficiency of HAC transfer to recipient cells ten fold. The improved MMCT protocol has been successfully tested on several recipient cell lines, including human mesenchymal stem cells and mouse embryonic stem cells. Published 2021. This article is a U.S. Government work and is in the public domain in the USA. Current Protocols published by Wiley Periodicals LLC. Basic Protocol 1 : Insertion of a BAC containing a gene of interest into a single loxP loading site of alphoid tetO ‐HAC in hamster CHO cells Basic Protocol 2 : Microcell‐mediated chromosome transfer from donor hamster CHO cells to mammalian cells